Boron removal from metallurgical grade silicon using a FeCl2 molten salt refining technique - Jia B.J.; Wu J.J.; Ma W.H.; Yang B.; Liu D.C.; Dai Y.N. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The slag refining for boron removal from metallurgical grade silicon is a promising metallurgical process for producing solar grade silicon. In this paper, FeCl2 molten salt has been used as a new refining agent to remove boron from MG-Si. The effects of refining time and mass ratio of MG-Si to FeCl2 molten salt on boron removal have been investigated in detail. The results showed that boron can be efficiently removed in form of BCl3 and boron concentration in MG-Si was successfully reduced from 22×10-6 to 4×10-6 at 1823K for 2 h with the mass ratio of FeCl2 molten salt to MG-Si for 1.0. The rate equation of boron removal using FeCl2 molten salt was proposed and established in kinetic, which showed a large difference in removal limitation of boron compared with thermodynamics.